RADIOLARIAN AGES FOR THE SEDIMENTARY COVER OF SEVAN OPHIOLITE (ARMENIA, LESSER CAUCASUS) - Asatryan, Gayané; Danelian, Taniel; Sosson, Marc; Sahakyan, Lilit; Person, Alain; Avagyan, Ara; Galoyan, Ghazar (Ofioliti, 2010)
Age data of Armenian ophiolites are of great importance for understanding the palaeogeographic and geodynamic evolution of Tethys in the Caucasus area and for lateral correlations of Tethyan ophiolitic belts in the Middle East area. Moderately well-preserved radiolarian assemblages obtained during this study from the Sarinar section of eastern Armenia allow to investigate the sedimentary and volcanic history recorded in a ca. 30 m-thick radiolarite sequence associated with spilitic lavas of the Sevan ophiolitic suture zone.The latest Bajocian-early Bathonian assemblage yielded from a sample situated close to the base of the studied sequence suggests that radiolarian ooze accumulation took place on oceanic crust of late Middle Jurassic age (probably Bajocian). Several tuffite levels are intercalated within the lower to middle part of the radiolarite sequence; a late Bathonian-early Oxfordian assemblage from a sample taken just below the uppermost tuffitic bed, suggests that during this time the oceanic domain of Sevan ophiolites was close to subaerial volcanic activity.